Badanie (rozumienie) szkoły w perspektywie hermeneutycznej = The understanding of school in the hermeneutic perspective - Baryluk, Marzena (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article focuses on schools and its programs. How understand the texts which the schools address us? What we can find in its programs?
Keywords: hermeneutyka; szkoła; badania